The Financial Healthiness of Working Capital Management and Profitability Analysis of Select Steel Companies in India - Venkatesan, T.; Nagarajan, S. K. (Gyan Management Journal, 2017)
The intention of this paper was to study the relationship between working capital management strategy of a firm and its profitability analysis. The fixed effects estimation on select steel companies of India. Financial healthiness has been utilize as a determine of the working capital management, while gross operating profit is used as a substitute for a firm’s profitability analysis. The results reveal that cash conversion cycle of a company has a negative correlation with its profitability. The results also suggest that managers can improve the performance by diminishing the number of day’s receivables and increasing the number of day’s payables. Besides, the outcomes demonstrate that the working capital strategies ought to be formulated taking worldwide macroeconomic circumstances into concern. The findings emphasize the significance of efficient working capital management practices to improve the profitability of steel companies.